Beyond the known functions of the CCR4‐NOT complex in gene expression regulatory mechanisms: New structural insights to unravel CCR4‐NOT mRNA processing machinery. (9th August 2016) - Ukleja, Marta; Valpuesta, José María; Dziembowski, Andrzej; Cuellar, Jorge
Abstract : Large protein assemblies are usually the effectors of major cellular processes. The intricate cell homeostasis network is divided into numerous interconnected pathways, each controlled by a set of protein machines. One of these master regulators is the CCR4‐NOT complex, which ultimately controls protein expression levels. This multisubunit complex assembles around a scaffold platform, which enables a wide variety of well‐studied functions from mRNA synthesis to transcript decay, as well as other tasks still being identified. Solving the structure of the entire CCR4‐NOT complex will help to define the distribution of its functions. The recently published three‐dimensional reconstruction of the complex, in combination with the known crystal structures of some of the components, has begun to address this. Methodological improvements in structural biology, especially in cryoelectron microscopy, encourage further structural and protein‐protein interaction studies, which will advance our comprehension of the gene expression machinery. Abstract : The CCR4‐NOT complex, a master regulator in the control of protein expression, is involved in the regulation of RNA metabolism at many steps, from synthesis to degradation. The combination of different structural techniques (X‐ray crystallography, NMR, cryoelectron microscopy) has allowed to generate a quasi‐atomic model of this large macromolecular complex.